Bias in adjudication: Investigating the impact of artificial intelligence, media, financial and legal institutions in pursuit of social justice. - Kashif Javed; Jianxin Li (PLoS ONE)
The latest global progress report highlights numerous challenges in achieving justice goals, with bias in artificial intelligence (AI) emerging as a significant yet underexplored issue. This paper investigates the role of AI in addressing bias within the judicial system to promote equitable social justice. Analyzing weekly data from January 1, 2019, to December 31, 2023, through wavelet quantile correlation, this study examines the short, medium, and long-term impacts of integrating AI, media, international legal influence (ILI), and international financial institutions (IFI) as crucial factors in achieving Sustainable Development Goal 16 (SDG-16), which focuses on justice. The findings indicate that AI, media, ILI, and IFI can help reduce bias in the medium and long term, although their effects appear mixed and less significant in the short term. Our research proposes a comprehensive policy framework that addresses the complexities of implementing these technologies in the judicial system. We conclude that successfully integrating AI requires a supportive global policy environment that embraces technological innovation, financial backing, and robust regulation to prevent potential disruptions that could reinforce inequalities, perpetuate structural injustices, and exacerbate human rights issues, ultimately leading to more biased outcomes in social justice.